Cas13d: A New Molecular Scissor for Transcriptome Engineering - Gupta, Rahul; Ghosh, Arijit; Chakravarti, Rudra; Singh, Rajveer; Ravichandiran, Velayutham; Swarnakar, Snehasikta; Ghosh, Dipanjan (Frontiers in Cell and Developmental Biology, 2022)
The discovery of Clustered Regularly Interspaced Palindromic Repeats (CRISPR) and its associated Cas endonucleases in bacterial and archaeal species allowed scientists to modify, utilize, and revolutionize this tool for genetic alterations in any species. Especially the type II CRISPR-Cas9 system has been extensively studied and utilized for precise and efficient DNA manipulation in plant and mammalian systems over the past few decades. Further, the discovery of the type V CRISPR-Cas12 (Cpf1) system provides more flexibility and precision in DNA manipulation in prokaryotes, plants, and animals. Furthermore, much effort has also been employed to utilize the above CRISPR tools for RNA manipulation but the ability of Cas9 and Cas12 to cut DNA involves the nuisance of off-target effects on genes and may not be employed in all RNA-targeting applications. Therefore, the search for new and diverse Cas effectors which can precisely detect and manipulate the targeted RNA begins and this led to the discovery of novel RNA targeting class 2, type VI-CRISPR-Cas13 system. CRISPR-Cas13 system is RNA-guided single Cas13 effector CRISPR nucleases that solely target single-stranded RNA (ssRNA) in a programmable way without altering DNA. Cas13 effectors family comprises of four subtypes (a-d) and each subtype has distinctive primary sequence divergence except the two consensuses Higher eukaryotes and prokaryotes nucleotide-binding domain (HEPN) that includes RNase motifs i.e. R-X4-6-H. The two HEPN domains are solely responsible for executing targetable RNA cleavage activity. However, recent studies have shown that Cas13d exhibits higher efficiency and specificity in cleaving targeted RNA in the mammalian system compared to other Cas13 endonucleases of the Cas13 enzyme family. Further, Cas13d has shown additional advantages over other Cas13 variants in structurally as well as functionally which makes it a prominent and superlative tool for RNA engineering and editing. Therefore considering the above advantages of CRISPR Cas13d over the previously characterized other Cas 13 subtypes, in this review we encompass the structural and mechanistic properties of type VI CRISPR-Cas13d systems, an overview of the current reported various applications of Cas13d, and future prospects to improve Cas13d based tools for diagnostic and therapeutic purposes.